Report on the Expert Forum on using Information Technology to Facilitate Uptake and Impact of Colorectal Cancer Screening Guidelines - Maida J Sewitch; Mengzhu Jiang; Alan N Barkun; David Armstrong; Donna Manca; Peter Rossos; Barry Stein (Canadian Journal of Gastroenterology)
The present report summarizes the proceedings of the pan-Canadian Expert Forum on Using Information Technology to Facilitate Uptake and Impact of Colorectal Cancer Screening Guidelines, which was held in Montreal, Quebec, November 18 to 19, 2011. The meeting assembled a multidisciplinary group of family physicians, gastroenterologists, nurses, patients, foundation representatives, screening program administrators and researchers to discuss the development of a mechanism or strategy that would permit the collection of comparable data by all colorectal cancer (CRC) screening programs, which would not only support the needs of each program but also provide a national perspective. The overarching theme of the meeting was ‘designing a national approach to computerized electronic data collection and dissemination for CRC screening that would improve knowledge transfer across the continuum of preventive health care’. The forum encouraged presentations on clinical, research and technical topics. The meeting fostered valuable cross-disciplinary communication and delivered the message that it is essential to develop a national health informatics approach for CRC screening data collection and dissemination to support provincial CRC screening programs.